Safety and human resource law for the safety professional - Schneid, Thomas D.; Schneid, Shelby L. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
The purpose of this text to provide a "one stop" source for safety professionals to acquire a general knowledge regarding not only the OSH Act but also laws and standards which impact the safety profession on a daily basis. The safety professional today does not work in a vacuum and decision-making can be impacted by a myriad of other laws. This new book will be the safety professional's "go to" text to acquire a quick understanding of the particular law potentially impacting his/her daily activities. Features Includes safety laws as well as human resource laws Presents new OSHA whistleblower actions Encompasses updated contractor requirement under Wage and Hour laws Covers new NLRA decisions and actions Addresses e-commerce and social media issues involving the safety function
OCLC-licensed vendor bibliographic record.
Keywords: Industrial safety -- Law and legislation -- United States; LAW / Administrative Law & Regulatory Practice; TECHNOLOGY / Industrial Health & Safety; LAW / Environmental; BUSINESS & ECONOMICS / Human Resources & Personnel Management